Characterization of reemergent anti‐B red blood cell antibodies in a patient with recurrent acute myeloid leukemia with ABO‐incompatible allogeneic peripheral blood stem cell transplantation. Issue 11 (10th September 2019) - Tajima, Katsushi; Takizawa, Kazuya; Yasuda, Takeshi; Tsumanuma, Riko; Okuyama, Shuhei; Kumagai, Hiroaki; Omoto, Eijiro; Okumura, Wataru
Abstract: BACKGROUND: Isohemagglutinins against ABO antigens absent on both recipient and donor red blood cells (RBCs) increase or decrease after ABO‐incompatible hematopoietic stem cell transplantation (HSCT). However, few reports have described the changes in the isohemagglutinin titers and the characteristics in patients with recurrent hematologic conditions after ABO‐incompatible HSCT. CASE REPORT: A 59‐year‐old female with acute erythroid leukemia received a peripheral blood stem cell transplant from her HLA‐haploidentical daughter. The patient was typed as group O with anti‐ A (4+) and B (4+) isohemagglutinins, while the donor was typed as group B. The bone marrow cells achieved complete donor cell chimerism on Day 13 after HSCT. On Day 120, the patient showed 97% B RBC type with persistent anti‐A (3+) and without anti‐B antibodies. On Day 375, her leukemia relapsed, and recipient type O RBCs and anti‐B antibodies sequentially reemerged. However, clinicolaboratory hemolysis and erythroid aplasia were not detected in the patient. RESULTS: The post‐HSCT sera agglutinated the allo B RBCs, but not the donor B RBCs, while the pre‐HSCT sera agglutinated both RBCs. The burst‐forming/colony‐forming units of erythroid formation from the donor peripheral blood stem cells were impaired by only the pre‐HSCT sera and not by the post‐HSCT sera. CONCLUSION: To our knowledge, this is the first report investigating the characteristic changes of isohemagglutinins between the pre‐ and post‐HSCT sera in a patient with recurrent acute myeloid leukemia. The present study suggests that the plasma cells producing anti‐donor B RBCs in the patient have been selectively eliminated or induced into an anergic state by the post‐HSCT immunologic reconstruction.